Caracterização da expressão de genes antiapoptóticos e de resistência a múltiplas drogas na resposta a terapia de indução em pacientes com leucemia linfoblástica aguda - Pereira, Daniele de Sá (2023)
Despite therapeutic advances, 25% of children with acute lymphoblastic leukemia (ALL) relapse during treatment due to various intrinsic cellular switches. Studies report that the high expression of anti-apoptotic genes and resistance to multiple drugs are types associated with therapeutic failures in several neoplasms, including leukemias. However, there is a lack of studies demonstrating the influence of the expression of these genes on the response to induction therapy in patients with B-cell acute lymphoblastic leukemia (B-ALL). Thus, the present study aimed to characterize the expression of multi-drug resistance genes (ABCB1, ABCC1, MVP) and antiapoptotic genes (TP53 and BCL2) in the clinical prognosis of patients with B-ALL projected at Fundação Hospitalar de Hematologia e Hemoterapia do Amazonas (HEMOAM) and compare their expression levels to those of healthy children. A prospective longitudinal study was carried out, in which bone marrow (BM) and peripheral blood (SP) were included in 17 pediatric patients with BALL, of general age group and gender, during induction therapy, being collected at diagnosis (D0) and at the end of therapy (D35). In addition, a SP sample was collected from 17 healthy children, attended at the HEMOAM Foundation outpatient clinic. Detection of gene expression (ABCB1, ABCC1, MVP, TP53, BCL2) was performed using the quantitative real-time PCR (qPCR) technique using Taqman expression probes. It was observed that the anti-apoptotic genes BCL2 and TP53 were more expressed in patients with B-ALL compared to healthy subjects in SP. Furthermore, levels of expression of resistance genes ABCB1, ABCC1 and MVP decreased in the bone marrow at D35 of the induction therapy, counteracting the increase in expression of ABCC1 and MVP at D35 compared to D0 of reference blood from those patients. Finally, we observed that healthy individuals expressed higher levels of MVP compared to patients with ALL. Finally, we observed that the evaluation of the expression of the ABCB1, ABCC1, MVP, BCL2 and TP53 genes can help in the evaluation of the prognosis of these patients, contributing to the detection of possible molecular biomarkers and the creation of targeted therapies in addition to current chemotherapy. However, future investigations are necessary for a better understanding of the impact of the expression of these genes on medullary remission in these patients, generating data that contribute to an increase in the survival rate in A-ALL.